ANALISIS KOMPOSISI DAN KELIMPAHAN BAKTERI Vibrio sp. PADA BUDIDAYA UDANG VANNAMEI (Litopenaeus vannamei) SISTEM INTENSIF - Suprakto, Bambang; Lestari, Mitaqul Dwi; Aulia, Deni; Hakimah, Nisa; Wartini, Sri (Jurnal Perikanan Unram, 2024)
Vannamei shrimp (Litopenaeus vannamei) is the most economical species of shrimp. The presence of Vibrio sp. bacteria in intensive shrimp farming systems as the cause of Vibriosis disease causes losses both socially and economically. This study aims to analyze the composition and abundance of Vibrio sp. Bacteria in a Vannamei shrimp culture intensive system. Samples were taken in the form of cultivation media (water) and shrimp (hepatopancreas and intestine) from 4 different ponds, 2 ponds each in Banyuwangi Regency and Sumenep Regency, East Java. The analysis was performed using TCBS agar media. Vibrio sp. bacteria that grow on bacterial colonies are green and yellow with rounded shapes and intact edges. The composition of bacteria that grow is more yellow colonies (90.4%) than the number of green colonies (9.60%). The abundance of Vibrio sp. bacteria in the Vannamei shrimp farming intensive system media found in this study ranged from 7.75 x 102 – 15.80 x 102 CFU/ml. While the abundance of Vibrio sp. Bacteria in hepatopancreas and shrimp intestine samples is 1.0 x 101 - 3.02 x 104. The abundance of bacteria is not affected by the age of shrimp cultivation. The amount of Vibrio sp. in intensive Vannamei shrimp system farming is still within safe limits.